Estudio longitudinal ecocardiográfico de variables y rendimiento en atletas de elite de media y larga distancia - Legaz Arrese, A.; Serrano Ostariz, E.; Lafuente Bergos, D. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2001)
The purpose is to establish the relationship between echocardiographic variables and performance achieved over several years and to determine the relationship between the degree of dilation and of cardiac hypertrophy. An echocardiographic study was carried out on 12 men and 12 women to compete at top-class level in long and middle distance events .They underwent echocardiographic measurements at least 4 times. An echocardiographic study was carried out each athlete in each competitive season. The best performance carried out by the athlete each year was chosen. LVV/BS (end-diastolic) has a close relationship with performances in sport, and a highly significant correlation can be found (r > 0.80) in several athletes, the highest record being very close to that of the best performance in almost all the athletes. New results show a negative relationship between hypertrophy evolution (PWT and SWT), and a better competition speed (r > -0.70) in some of the atheletes.